Estimating Dynamic Properties of RC Frame Structures with Various Infill Materials for Quick Assessment - Julailati, Abdulrahman (Eastern Mediterranean University, 2022)
The effect of infill walls on frame rigidity is usually not considered in the performance assessment of structures nor the fundamental period, where infill walls would affect both the performance level and the structure's period negatively or positively depending on their plan and elevation distribution. Moreover, the need for a quick assessment tool to predict the performance level of structures is essential, especially considering infill wall effects. Therefore, buildings were designed according to the Turkish Seismic Code for Buildings 2018 (TSCB-2018) and the Requirements for Design and Construction of Reinforced Concrete Structures Code (TS-500). The number of analyzed models was 336, each with different combinations of peak ground acceleration, soil type, infill material, and infill walls layouts. The data in the Artificial Neural Network (ANN) models used analysis outcomes collected, such as the fundamental period, target displacement, and performance level, as a target, training, and validation data. Furthermore, for performance assessment, the commercial program Seismostruct 2022 was used for nonlinear static analysis (pushover analysis), while Matlab 2018 was used for the creation of neural network models. Bayesian regularization backpropagation was used for all ANN models. ANN models showed excellent accuracy in all three models: period, performance, and target displacement. The models' accuracy obtained was as follows: in the performance level model at 96.15%, while for the fundamental period of the structure, it was 99.99% and lastly, the target displacement was 99.66%. Keywords: ANN, Fundamental Period, Infill Wall, Performance, Target Displacement.

Dolgu duvarların çerçeve rijitliği üzerindeki etkisi, dolgu duvarların plan ve kot dağılımına bağlı olarak hem performans seviyesini, hem de yapının periyodunu olumsuz veya olumlu yönde etkileyeceği genellikle dikkate alınmaz. Ayrıca, özellikle dolgu duvar etkileri göz önüne alındığında, yapıların performans düzeyini tahmin etmek için hızlı bir değerlendirme aracına duyulan ihtiyaç esastır. Bu nedenle binalar Türk Deprem Yönetmeliği 2018 (TSCB-2018) ve Betonarme Yapıların Tasarım ve Yapım Kuralları Yönetmeliğine (TS-500) göre tasarlanmıştır. Analiz edilen 336 modelin, her biri farklı maksimum yer ivmesi, zemin tipi, dolgu malzemesi ve dolgu duvar yerleşimi kombinasyonlarına sahiptir. Bu analiz sonuçlarına göre yapının periyodunu, hedef yer değiştirmesini ve performans seviyesini verecek Yapay Sinir Ağı (YSA) modelleri oluşturulmuştur. Ayrıca, statik itme analizi (pushover) yöntemiyle performans değerlendirilmesi için, Seismostruct 2022 programı, Yapay Sinir Ağı modellerinin oluşturulması için de Matlab 2018 kullanıldı. Tüm YSA modelleri için Bayes düzenlileştirme geri yayılımı kullanılmıştır. YSA modelleri, üç modelde de mükemmel doğruluk gösterdi: periyot, performans ve hedef yer değiştirme. Elde edilen modellerin doğruluğu şu şekildedir: performans düzeyi modelinde %96,15 iken, yapının temel periyodu için %99,99 ve son olarak hedef yer değiştirme %99,66 olmuştur. Anahtar kelimeler: YSA, periyot, dolgu duvar, performans, hedef yer değiştirme
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2022. Supervisor: Assoc. Prof. Dr. Giray Özay.
Keywords: Thesis Tez; Civil Engineering Department; Earthquake resistant design; Earthquake Resistant Design--Steel Frame Construction; Buildings--Earthquake effects; Earthquake; Seismic design; Infill Walls; ANN; Fundamental Period; Infill Wall; Performance; Target